Punjab State the Revised Second Five-Year Plan - Planning Commission (Planning Commission, 1955)
Broadly, the result of the discussions with the Planning Commission has revealed that after taking the maximum advantage of any permissible manipulations regarding methods of accounting, and allowing for a substantial measure of additional taxation, the State will at best have a small contribution to make for the financing of schemes on the Revenue Account. This position is substantially the result of the development already undertaken, and is more particularly the result of increased burden on the State Revenues from Schemes where the Central Government contribution has decreased proportionately with the passage of time. Several schemes have to be carried on now wholly or almost wholly on State resources, which were previously financed wholly or almost wholly by the Centre. The Punjab Government have, in consultation with the Planning Commission, carefully and exhaustively examined the possibilities of increased resources from taxation, and those decided on, should circumstances be favourable for enforcing a higher measure of taxation, will be in view of the tax burden already borne by the people, the result of tremendous effort. In assessing this effort account must be taken of the substantial contributions expected on a voluntary basis, which are estimated at over 839 lakhs during the Second Plan period. It seems clear, therefore, that even^on an optimistic assessment, assistance to the State Government for financing Revenue Account Schemes must be made available
Government of India Planning Commission
Government of India Planning Commission
Keywords: Revised Second Five-Year Plan of the Punjab forwarded; Documents in which Plan presented to the Commission; Phasing of Expenditure; Total Position regarding Financing; Foreign Exchange Expenditure; Plan Expenditure; Public Contributions; Minor Irrigation Projects; Animal Husbandry